The missing links: A global study on uncovering financial network structures from partial data - Kartik Anand; Iman van Lelyveld; Ádám Banai; Soeren Friedrich; Rodney Garratt; Grzegorz Hałaj; Jose Fique; Ib Hansen; Serafín Martínez Jaramillo; Hwayun Lee; José Luis Molina-Borboa; Stefano Nobili; et al. (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
Capturing financial network linkages and contagion in stress test models are important goals for banking supervisors and central banks responsible for micro- and macroprudential policy. However, granular data on financial networks is often lacking, and instead the networks must be reconstructed from partial data. In this paper, we conduct a horse race of network reconstruction methods using network data obtained from 25 different markets spanning 13 jurisdictions. Our contribution is two-fold: first, we collate and analyze data on a wide range of financial networks. And second, we rank the methods in terms of their ability to reconstruct the structures of links and exposures in networks.
Keywords: G20; L14; D85; C63; 330; Network reconstruction; market structure; intermediation